2016
DOI: 10.1080/17441692.2016.1241816
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vision impairment and self-reported barriers to vision care: The views of elders in Nuwara Eliya district, Sri Lanka

Abstract: FGDs: focus group discussions; GBD: global burden of disease; NCDs: non-communicable diseases; VI: vision impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…The difference in time, settings, and methodology could have led to this disparity. Cost, as a leading barrier to cataract surgery reported in our study, was concordant to that reported among elders in the Nuwara Eliya District, Sri Lanka [ 88 ], as a leading barrier to eye care services. Kumar et al [ 89 ] reported that 88.9% of surveyed subjects attending an outpatient unit in Uttar Pradesh, India, complained about the cost of cataract surgery and 59.1% complained about the fear of losing sight.…”
Section: Discussionsupporting
confidence: 90%
“…The difference in time, settings, and methodology could have led to this disparity. Cost, as a leading barrier to cataract surgery reported in our study, was concordant to that reported among elders in the Nuwara Eliya District, Sri Lanka [ 88 ], as a leading barrier to eye care services. Kumar et al [ 89 ] reported that 88.9% of surveyed subjects attending an outpatient unit in Uttar Pradesh, India, complained about the cost of cataract surgery and 59.1% complained about the fear of losing sight.…”
Section: Discussionsupporting
confidence: 90%
“…However, lack of time and someone to accompany participants to the facility was an issue, particularly for those with visual impairment. Fear of surgery was not an important barrier unlike in a previous study [14]. The chronic nature of many of the conditions experienced by patients over a long period of time may be one reason why eye care was not sought [21], as demonstrated in this study where persons with acute conditions like foreign body/eye injury, dry eye and pain had higher rate of seeking care.…”
Section: Discussionmentioning
confidence: 64%
“…and extrinsic factors (cost of care, transportation links, perceived efficacy of treatment and past experience with the health system) [13]. In low and middle-income countries (LMICs) patients' demand for eye care is often restricted by the limited number of eye care facilities, particularly those at secondary and tertiary levels, resulting in increased time and transport costs required for access, as was recently reported from Sri Lanka [14].…”
Section: Introductionmentioning
confidence: 99%